Determinants of Long-Term Performance of Initial Public Offering: Evidence from Indonesia Stock Exchange - Eka Yuyan, Febby; Adrianto, Fajri; Hamidi, Masyhuri (Riviera Publishing, 2022)
Introduction: Companies conducting initial public offerings have two main anomalies in stock exchanges around the world, namely underpricing (short-term performance) and poor long-term performance (poor long-run term performance). One of the factors that can provide information on the performance of an initial public offering company is the initiation of dividends, the age of the company, and the reputation of the underwriter. The purpose of this study is to analyze the long-term performance of Indonesian IPOs made during the period from 2012 to 2018. Method: This type of research is quantitative research, and the type of data used is secondary data. The population in this study are all initial public offering companies listed from 2012 to 2018. The sampling technique is non-probability sampling. The data analysis technique used SPSS 24. Result: IPO companies that experienced a positive initial return of 78% consisting of 139 companies, this was an advantage for investors while underpricing for the company while experiencing a negative initial return of 22% consisting of 40 companies. The initiation dividend has a coefficient (B) of -0.023 and a significant value of 0.349, indicating that the initiation dividend has a negative and insignificant effect on the long-term stock performance of IPO companies. The variable age of the company has a coefficient value (B) of 0.001 with a significance value of 0.049 which means that the age of the company has a positive and significant effect on buy and hold abnormal returns. The results of testing the influence of underwriter reputation1, underwriter reputation2, underwriter3 reputation, and underwriter reputation4 have no significant effect on the long-term stock performance of IPO companies. Conclusion: In general, the results of the long-term performance of IPOs in Indonesia from 2012 to 2018 during the three years after the IPO found negative abnormal results.